SAT0187 Tocilizumab Standard Dose is an Overtreatment with Regard to Systemic IL-6 Receptor Blockade in Rheumatoid Arthritis. (9th June 2015) - Kneepkens, E.L.; van den Oever, I.A.; Plasencia, C.H.; Pascual-Salcedo, D.; van der Kleij, D.; Hart, M.; Nurmohamed, M.T.; Balsa, A.; Aarden, L.; Rispens, T.; Wolbink, G.J.
Abstract : Background: Tocilizumab (TCZ) inhibits interleukine-6 (IL-6) receptor resulting in inhibition of C-Reactive Protein (CRP) production, a surrogate marker for IL-6 receptor blockade. 1 Evolving evidence showed that pharmacokinetics (PK) of TCZ is probably influenced by target-binding. 2, 3 Objectives: To investigate PK of TCZ and the relationship between TCZ concentrations and disease activity in an observational cohort of rheumatoid arthritis (RA) patients. Methods: This prospective study consisted of 70 consecutive patients (The Netherlands, n=37; Spain, n=33) treated with TCZ 8 mg/ kg intravenously once per 4 weeks, monitored during 48 weeks. Disease activity was measured with CRP (mg/L) and Disease Activity Score of 28 joints (DAS28), using erythrocyte sedimentation rate (ESR)(mm/hr). TCZ serum trough concentrations and anti-drug antibodies were measured using an enzyme linked immunosorbent assay and an antigen binding test, respectively. Results: At baseline, mean DAS28 was 5.4±1.4 and median CRP, 6.9 (2.4-32.5). During 48 weeks, 19 patients discontinued TCZ prematurely due to: inefficacy (n=8), adverse events (n=8) or other reasons (n=3). TCZ concentrations above 1 mg/L were sufficient to normalize CRP production (<10 mg/L)(figure 1A ), which was achieved by 69-88% of patients, depending on time point of measurement. Of the 30 patients with increased CRP (>10 mg/L) at baseline, levels were normalized in 17 patients within 4 weeks. In 11 patients normalization of CRP took longer or CRP level was still increased at drop-out. Increased CRP levels in these 11 patients was accompanied by TCZ concentration below 1 mg/L. CRP data of 2 patients was missing. The concentration effect curve at week 24 (last observation carried forward for patients in whom week 12 was the last available visit) showed that the majority was overtreated with TCZ standard dose (figure 1B ). At week 24, median TCZ concentration was 11 mg/L (6-19) and mean ΔDAS28 was 2.4±1.6. Mean ΔDAS28 was lower in patients with TCZ concentrations below 1 mg/L vs above, respectively, -0.3±0.8 versus 2.8±1.4 (p<0.001) (independent sample t test). One patient had detectable anti-TCZ antibodies, in combination with low TCZ concentrations, at week 4. Conclusions: Increased CRP levels after baseline were accompanied by TCZ concentrations below 1 mg/L. This suggests that PK of TCZ is influenced substantially by target-binding and only marginally by immunogenicity, since, low TCZ concentration with anti-TCZ antibodies was found in only one patient. Due to the direct relationship between TCZ concentration and CRP inhibition, TCZ might be ideally suited for optimizing treatment via a personalised Therapeutic Drug Monitoring approach, aiming for serum concentrations within the optimal range for target blockade. This creates possibilities for dose reduction, since the majority of patients was overtreated with TCZ standard dose. References: Swaak. Scand J Rheumatol. 1988. Nishimoto. Blood. 2008. Nishina. Ann Rheum Dis. 2014. Disclosure of Interest: E. Kneepkens Speakers bureau: payment for lectures from Pfizer, I. Van Den Oever Speakers bureau: payments for lectures from BMS, C. Plasencia Grant/research support from: Pfizer, paid to institution, Speakers bureau: payment for lectures from Pfizer, D. Pascual-Salcedo Speakers bureau: payment for lectures from Pfizer, D. van der Kleij: None declared, M. Hart: None declared, M. Nurmohamed Consultant for: received consultancy fees from Abbott, Roche, Pfizer, MSD, UCB, SOBI and BMS, Speakers bureau: payment for lectures from Abbott, Roche and Pfizer, A. Balsa Grant/research support from: Pfizer, paid to institution, Consultant for: consultancy fees from Abbvie, Pfizer and MSD, Speakers bureau: payment for lectures from Abbvie, Roche and Pfizer, L. Aarden: None declared, T. Rispens Speakers bureau: received payment for lectures from AbbVie and Pfizer, G. Wolbink Grant/research support from: Pfizer, paid to institution, Speakers bureau: payments for lectures from Pfizer, Amgen, AbbVie, UCB and BMS.